The Advanced Virgo detector. (April 2015) - Acernese, F; Adams, T; Agathos, M; Agatsuma, K; Allocca, A; Astone, P; Ballardin, G; Barone, F; Barsuglia, M; Basti, A; Bauer, Th S; Bavigadda, V; et al.
Abstract: The Advanced Virgo interferometer is the upgraded version of the Virgo detector having the goal to extend by a factor 10 the observation horizon in the universe and consequently increase the detection rate by three orders of magnitude. Its installation is in progress and is expected to be completed in late 2015. In this proceeding we will present the scheme and the main challenging technical features of the detector and we will give an outline of the installation status and the foreseen time schedule which will bring Advanced Virgo to its full operation.